Professional health : Obesity status and 24-hours diet recall of health-staff working at selected three primary care clinics in Kuantan, Pahang - Tin, Myo Han; Md Aris, Mohd Aznan; Mohd Shukri, Nor Azwani; Osman, Iskandar Firzada; M. D., Thuraiappah; Abdullah, Fa’iza; Sahrin, Saidatul Nabilah; Ismail, Nur Athirah; Mazubir, Nizatul Nuraih (2016)
Obesity statics in Malaysia rank sixth with highest adult obesity rate in Asia. Therapeutic Lifestyle-change diet (TLC-Diet) is advised by health practitioners to over-weight/obese patients as one component of lifestyle modification therapy. However, there is limited data on obesity-status and diet-pattern among health-practitioners who are dealing with obese-patients in primary-care.